Lipase-catalyzed preparation, bioavailability and functional properties of a DHA-enriched tuna oil - Yu, Jingwen; Shen, Cai; Chen, Haohui; Luo, Min; Zhang, Linshang; Liu, Yanan; Xu, Feng; Tan, Chin-Ping; Cheong, Ling-Zhi (Elsevier BV, 2024)
Docosahexaenoic acid (DHA) in the form of triacylglycerols (TAG) are widely recognized for their health benefits. As naturally occurring DHA in the form of TAG are limited, this work developed and optimized a Candida rugosa lipase-catalyzed selective hydrolysis process to enrich DHA in tuna oil. The DHA-enriched tuna oil produced at optimal conditions (lipase concentration of 4 %, ratio of water to tuna oil of 1:3, reaction temperature of 55°C) contained 46.12 % of DHA, in which 55.24 % of DHA was located in sn-2 position of the glycerides. In-vitro bioavailability test shows, the DHA-enriched tuna oil (7.89 %) had significantly higher cellular uptake of DHA as compared to unprocessed oil. The DHA-enriched oil demonstrated increased intracellular oxidation and mitochondrial damage of Caco-2 cell.